2019
DOI: 10.1038/s41467-018-08200-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the landscape of focal amplifications in cancer using AmpliconArchitect

Abstract: Focal oncogene amplification and rearrangements drive tumor growth and evolution in multiple cancer types. We present AmpliconArchitect (AA), a tool to reconstruct the fine structure of focally amplified regions using whole genome sequencing (WGS) and validate it extensively on multiple simulated and real datasets, across a wide range of coverage and copy numbers. Analysis of AA-reconstructed amplicons in a pan-cancer dataset reveals many novel properties of copy number amplifications in cancer. These findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
337
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(340 citation statements)
references
References 35 publications
(40 reference statements)
3
337
0
Order By: Relevance
“…EcDNA can arise during genome reshuffling events like chromothripsis and are subsequently amplified 2,3 . This partially explains why such circular DNAs can consist of several coding and non-coding distant parts of one or more chromosomes 4 .…”
Section: Introductionmentioning
confidence: 99%
“…EcDNA can arise during genome reshuffling events like chromothripsis and are subsequently amplified 2,3 . This partially explains why such circular DNAs can consist of several coding and non-coding distant parts of one or more chromosomes 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Performance-wise, low-coverage WGS consistently showed high concordance with microarray and high-coverage WGS in our analysis. It As WGS studies become less expensive, we foresee that in the future low-coverage WGS may prove to be replacing clinical microarray testing for cancers 33 , developmental disabilities, congenital anomalies [34][35][36] , autism spectrum disorder 37 , and many other genetic diseases 29 . Citing the benefits of WGS, a recent study compared the performance of low-coverage WGS versus microarrays on rare and undiagnosed cases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent genome profiling studies of both healthy and cancerous human tissues found a high prevalence of nuclear extra-chromosomal DNA (ecDNA) [1,2,3,4]. ecDNA occurs during episodes of chromosomal instability and contributes to cancer initiation and treatment resistance [5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…ecDNA occurs during episodes of chromosomal instability and contributes to cancer initiation and treatment resistance [5,6,7,8,9]. Double minute oncogene amplifications exist in 31.7% of all neuroblastoma and highly amplified extra-chromosomal KRAS copies appear at relapse of anti-EGFR targeted therapies [1,4,9]. Yet, the evolutionary fade Figure 1.…”
Section: Introductionmentioning
confidence: 99%